Sinergi Politik : Lembaga Penyelenggara Pemilihan Umum - ST. Ika Noerwulan Fraja (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
General election is free of charge honest and fair which is held every five years and who became the organizer of the election it must be a national commission, exemplary or independent. In its operation it is impossible KPU to work independently because the election require oversight of the agency, therefore is needed other institutions that also independent to supervise the performance of KPU, namely DKPP and BAWASLU. The type of the research that used in this research is normative legal research. normative legal research is a law research that examines rules or norms. Using the legislation approach method, historical approach, and conceptual approach. The legislation approach, means by examining all laws relating with legal issues. Historical approach, means by examining the background on the issues at hand. While the conceptual approach depart from the views and doctrines developed in the science of law. This research aims to determine and to understanding how the regulation and reformulation concept or ordering as new offer related the election organizing in Indonesia.